Accuracy of presumed uveal melanoma diagnosis before alternative therapy. - Char, D H (1995)
AIMS/BACKGROUND--This study was performed to ascertain the diagnostic accuracy rate of non-invasive tests in patients with presumed uveal melanomas scheduled to be treated with either irradiation or cyclochoroidectomy. METHODS--One hundred consecutive patients who had non-invasive tests followed by fine needle aspiration biopsy (FNAB) as prior alternative treatment were analysed retrospectively. RESULTS--In 86 cases the diagnosis of uveal melanoma was confirmed on FNAB. In five cases false negative results were obtained. In nine patients a diagnosis other than a uveal melanoma was made on the basis of cytopathology. No significant morbidity and no evidence of tumour spread occurred. CONCLUSION--In presumed uveal melanomas eligible for treatment with alternative therapies, the diagnostic accuracy of non-invasive tests is not as good as with larger tumours that require enucleation. Fine needle aspiration biopsy data resulted in correct management of 9% of cases that were thought to have uveal melanomas on non-invasive tests, but had other lesions on cytopathological evaluation.